Magnetotelluric exploration of the Wagner Basin, Gulf of California, Mexico: Evidence for an axial magma chamber and hydrothermal circulation. (April 2020) - Esquivel, Thalia Avilés; Flores, Carlos; Ortega, Valeria Reyes; Constable, Steven; Gómez-Treviño, Enrique; González-Fernández, Antonio
Abstract: Different geological and geophysical disciplines have suggested the Wagner Basin as a promising location of geothermal resources. As a reconnaissance tool Magnetotelluric (MT) data were measured at 10 sites along a profile over this basin in the northern Gulf of California. The subsurface distribution of electric resistivity was estimated with two-dimensional smooth inversion using the apparent resistivities and phases from both field polarizations. We found a deep conductor underneath the center of the basin, interpreted as a region of partial melt feeding the accretion zone of this incipient oceanic crust. From six MT sites with close-by heat flow measurements, we also found a positive correlation between the interpreted shallow (first 100 m) low resistivities and high heat flows. This shows that the MT method can be used to map submarine heat sources. Highlights: The magnetotelluric marine method was used to explore the northern Gulf of California with geothermal purposes. The 2D resistivity model reveals a deep conductor under the center of the Wagner basin likely produced by partial melting. There is a good correlation between high heat flow values and shallow low resistivities estimated from the magnetotelluric data.